Reasoning with God : reclaiming shari'ah in the modern age - Abou El Fadl, Khaled, 1963- (Maryland : The Rowman & Littlefield Publishers, 2014)
In light of recent concern over Shari'ah, such as proposed laws to prohibit it in the United States and conflict over the role it should play in the new Egyptian constitution, many people are confused about the meaning of Shari'ah in Islam and its role in the world today. In Reasoning with God, renowned Islamic scholar Khaled Abou El Fadl explains not only what Shari'ah really means, but also the way it can revitalize and reengage contemporary Islam. After a prologue that provides an essential overview of Shari'ah, Abou El Fadl explores the moral trajectory of Islam in today's world. Weaving powerful personal stories with broader global examples, he shows the ways that some interpretations of Islam today have undermined its potential in peace and love. Rather than simply outlining challenges, however, the author provides constructive suggestions about how Muslims can reengage the ethical tradition of their faith through Shari'ah. As the world's second largest religion, Islam remains an important force on the global stage. Reasoning with God takes readers both Muslim and non-Muslim beyond superficial understandings of Shari'ah to a deeper understanding of its meaning and potential. --Provided by publisher.
An introduction to Shari'ah -- Part I. The Islamic dream and the chaos of the modern condition -- 1. Genesis : negotiating the Muslim and the Islamic -- 2. Awakening : reasonableness and Islam -- 3. Crisis : making sense of Shari'ah today -- 4. Repose : the Islamic between harmony and dissonance -- Part II. The culture of ugliness and the plight of modern Islam -- 5. Faulty paradigms in constructing the Islamic -- 6. Beyond Islamophobia -- 7. God the universal -- 8. What really went wrong -- 9. God, Shari'ah and beauty -- Part III. Reclaiming Shari'ah in the modern age -- 10. Shari'ah as reasoning with God -- 11. Beyond a reasonable Shari'ah -- 12. The Caliphate of humanity -- Concluding the journey : reclaiming the path to the self in God and the God in the self.
Includes bibliographical references and index
Keywords: Islam -- Customs and practices; Islam -- Rituals; Islamic law